STUDI KOMPARASI KARBURATOR KONVENSIONAL DENGAN KARBURATOR VAKUM PADA SEPEDA MOTOR YAMAHA MIO 110 - Inzhagi Zetta Bachtiar Wibowo; Kurniawan Joko Nugroho; Muhammad Priya Permana (Journal of Automotive Technology Vocational Education, 2026)
This study aims to compare engine performance, fuel consumption efficiency, and working characteristics between the PWK 28 conventional carburetor and the standard Ori Yamaha Mio vacuum carburetor (CV) on a Yamaha Mio 110 cc motorcycle. The research method was carried out through direct testing by measuring fuel consumption using a 250 ml measuring cup at a variation of engine revs of 1000 rpm, 1500 rpm, and 2000 rpm for 5 minutes. Each test is repeated three times to obtain more accurate average data. The results showed that the PWK 28 conventional carburetor provided faster gas response, aggressive acceleration, and greater peak power at high revs, but its fuel consumption was more wasteful (approximately 81.1 ml at 1000 RPM; 107.4 ml at 1500 RPM; and 130.7 ml at 2000 RPM). In contrast, the standard Ori Yamaha Mio vacuum carburetor produces smoother gas draw, more stable engine power, and more efficient fuel consumption at all engine rev variations. Thus, PWK 28 is more suitable for use in vehicles with high performance or racing needs, while vacuum carburetors are more suitable for daily use that prioritizes efficiency and comfort.   Keywords: Conventional carburetor, vacuum carburetor, Yamaha Mio, fuel consumption, engine revs.